Mother Characteristics, Husband Support with Anxiety in Third Trimester Pregnant Women - Al Haq, Rifa Asmieza; Sartika, Rini; Sari, Ria Setia (Jurnal Ilmiah Kesehatan (JIKA), 2025)
Pregnancy is a natural process lasting approximately nine months, during which a woman carries an embryo and a growing fetus in her womb with the purpose of continuing the lineage. This process marks an important first step in the life of the next generation. Pregnancy is also a physiological phenomenon that causes changes in a woman's body, most of which are due to the body's response to the fetus. This study aims to explore the relationship between the anxiety levels experienced by third-trimester pregnant women and the support they receive from their husbands. The research was conducted at Tangerang District Hospital using a cross-sectional methodology and a descriptive correlational design. Primary data were gathered through questionnaires filled out by the participants. The study population comprised third-trimester pregnant women with gestational ages between seven and nine months. A sample of 110 subjects was selected using the accidental sampling technique, which is a type of nonprobability sampling. Data were analyzed using the chi-square test. The results showed a significant relationship between husband support and the level of anxiety experienced by third-trimester pregnant women at Tangerang District General Hospital (p-value = 0,001). Meanwhile, other variables such as age (p-value = 0,086), education level (p-value = 0,337), and parity (p-value = 0,162) did not show a significant relationship. Therefore, husband support plays an important role in reducing anxiety levels among third-trimester pregnant women.